Birth weight is inversely correlated with blood pressure: population-based study. Issue 11 (November 2020) - Al Salmi, Issa; Hannawi, Suad
Abstract : Background and method: The current representative national cross-sectional study examines the association of birth weight and blood pressure (BP) among the adult Australian population. Questions about birth weight were added to the second round of AusDiab study. Hypertension was defined based on WHO (≥140/90), and NCEP-ATPIII (≥130/85). Both definitions were examined against the continuous birth weight and dichotomous variable of low birth weight (LBW); less than 2.5 kg, adjusting for age, BMI, physical activity, smoking, alcohol intake and socioeconomic factors. Results: A total of 4502 respondents reported their birth weights with a mean (SD) of 3.37 (0.7) kg. Females with LBW had significantly higher mean SBP and DBP than those with normal birth weight. This relationship persisted with adjustments for various confounding factors. Males with LBW showed a trend towards a higher SBP and DBP, though NS, than normal birth weight more than 2.5 kg. LBW individuals, less than 2.5 kg were at higher risk for having high SBP hypertension at least 140/90 mmHg and at least 130/85 mmHg compared with those with normal birth weight. Among females, for each kilogramme of birth weight, there was a predicted decrease of 1.59 (0.7, 2.5) mmHg in SBP, P  = 0.001 and 0.85 (0.2, 1.5) mmHg in DBP, P  = 0.001; after adjustments for age, body size, physical activity, smoking status, alcohol intake and socioeconomic factors. Among males, for each kilogramme of birth weight, there was a decrease of 1.74 (0.7, 2.8) mmHg in SBP, P  = 0.002 and 1.06 (0.3, 1.9) mmHg in DBP, P  = 0.008 after adjustments for all confounding factor. Conclusion: This study has examined the association of birth weight and BP in a representative adult population. LBW was significantly associated with the risk of developing high BP.